2013
DOI: 10.1002/jms.3112
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the metabolism and toxicological detection of glaucine, an isoquinoline alkaloid from Glaucium flavum (Papaveraceae), in rat urine using GC‐MS, LC‐MSn and LC‐high‐resolution MSn

Abstract: Glaucine ((S)-5,6,6a,7-tetrahydro-1,2,9,10-tetramethoxy-6-methyl-4H-dibenzo [de,g]quinoline) is an isoquinoline alkaloid and main component of Glaucium flavum (Papaveraceae). It was described to be consumed as recreational drug alone or in combination with other drugs. Besides this, glaucine is used as therapeutic drug in Bulgaria and other countries as cough suppressant. Currently, there are no data available concerning metabolism and toxicological analysis of glaucine. To study both, glaucine was orally admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…The settings were the same as described previously by Meyer et al [10,18], briefly, a Thermo Fisher Scientific (TF, Dreieich, Germany) Dionex LC system coupled to the TF LTQ Orbitrap (OT) equipped with a HESI II source. Separation was performed by a TF Hypersil Gold (15×2.1 mm, 1.9 μm) and gradient elution.…”
Section: Gc-ms Apparatus For Identification Of the Phase I Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The settings were the same as described previously by Meyer et al [10,18], briefly, a Thermo Fisher Scientific (TF, Dreieich, Germany) Dionex LC system coupled to the TF LTQ Orbitrap (OT) equipped with a HESI II source. Separation was performed by a TF Hypersil Gold (15×2.1 mm, 1.9 μm) and gradient elution.…”
Section: Gc-ms Apparatus For Identification Of the Phase I Metabolitesmentioning
confidence: 99%
“…For identification of phase II metabolites, 1 mL urine (rat urine 20 mg/kg BW drug administration) was processed by SPE (C18) according to References [17] and [10]. Briefly, urine was diluted with 2 mL purified water before loading the sample on a previously conditioned (1 mL methanol, 1 mL water) Isolute Confirm C18 cartridge.…”
Section: Urine Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo metabolism of NPS was investigated in recent years by identifying the phase I and II metabolites using HRMS mainly in urine of humans and/or rats Welter et al 2013Welter et al , 2014aWelter et al , b, 2015aMeyer et al 2013bMeyer et al , c, d, e, 2014cMeyer et al , d, 2015Wink et al 2014Wink et al , 2015bWink et al , c, 2016Caspar et al 2015;Michely et al 2015;Welter-Luedeke and Maurer 2015) or in pics (Schaefer et al 2016). Some of these studies showed that the metabolism of rats was qualitatively comparable to that of humans as the rat metabolites could also be detected in authentic human urine from clinical or forensic case work Welter et al 2013Welter et al , 2015bMeyer et al 2013cMeyer et al , 2015Caspar et al 2015;Helfer et al 2015b;Wink et al 2015c).…”
Section: Hrms For Elucidation Of the Metabolite Structures And Formatmentioning
confidence: 99%
“…Lower doses tend to yield a dopaminergic-dominant result or stimulation, while higher doses result in a mu-opioid receptor-dominant effect, which eclipses the dopaminergic expression or physical and emotional hedonia and pain relief [12,24,35,36]. Many analytical approaches have been reported for the separation and identification of kratom, including GC and GC-MS [2,3,[37][38][39], LC and LC-MS [38,[40][41][42][43][44] and CE and CE-MS [43,45,46]. In this study, we report a rapid and effective method for quantification mitragynine and 7-hydroxymitragynine compounds in human urine matrix.…”
Section: Introductionmentioning
confidence: 99%